Mani's Metivta: Manichaean Pedagogy in its Late Antique Mesopotamian Context. (July 2021) - Han, Jae
Abstract: This article investigates the nature of Manichaean pedagogy as expressed through the late antique codices known as the Kephalaia of the Teacher and the Kephalaia of the Wisdom of my Lord Mani . By paying attention to a range of contextual cues that frame each moment of instruction, it first argues that much like their rabbinic and Christian neighbors, Mesopotamian Manichaeans did not study in academic institutions. Rather, instruction took place on an ad-hoc, individual basis, often based on happenstance events; there is no mention of a building dedicated to learning, a standard curriculum, or a semester schedule. This article then contextualizes this form of non-institutionalized Manichaean instruction by comparing three formulae found in the Kephalaia codices that have parallels in the Babylonian Talmud: the formula of Mani "sitting among" his disciples (or of his disciples "sitting before" Mani), of Mani's disciples "standing before" Mani, and of various people "coming before" Mani. In so doing, this article ultimately argues that the Babylonian Rabbis and Syro-Mesopotamian Manichaeans shared a common pedagogical habitus, one expressed through bodily comportment and hierarchy rather than through the imposition of institutional norms.